The Social City Urban development and housing projects in Berlin and Naples in the post-war era - A comparison: Theoretical models, implemented projects, social and political impacts today - Scopacasa, Antonello (Universitätsverlag der Technischen Universität Berlin, 2022)
In the post-war period, Berlin and Naples experienced a phase of profound changes, essentially influenced by external factors: the less rigid urban structure which had been ruined by World War II, resulting in severe changes in the social and economic structure, an uncritical reception and implementation of largely theoretical models of functionalism in urban planning, and in the design of the new public building interventions. On the one hand, between the 1940s and the 1980s, Berlin experienced a considerable loss in population, a political isolation and an urban splitting, as the urban planning institutions, deeply influenced by relevant politics, slowly and thoroughly changed the cityscape. On the other hand, Naples suffered from a new phase of immigration as well as from the parallel densification of the old suburbs and the physical expansion of the city limits without consistent and socially appropriate urban planning measures. This phase of change, so full of contrasts, coincided with the establishment of new democratic systems in the Federal Republic of Germany and Italy, and with the fundamental goal of socially adequate housing in both the West and the East. The research involved a series of historical analyses of the relationship between urban development and social housing for critical reflection and to allow an informed evaluation of the contemporary condition. In particular, it investigated housing settlements realised in Berlin and Naples in the first four decades of the post-war period, which corresponds to the period in which public housing was central in both political and urban planning terms. The book focuses on places of living, the city and the house. Consequently, it investigates the scale of the project and that of the intervention, the relationship between innovation and the cultural reception of urban phenomena and, again, between the stage of the project and the realisation and upkeep of the interventions, between democratic expectations and the adequacy of the administration system. These steps have a direct effect on the social identity that inspires, structures and transforms the planned and then built city, that continuous dialogue between form and content (the past) that occurs, in general, through progressive and mutual adaptations. In the selection of the case studies, we have favoured interventions on the "periphery," which are those in which theoretical and aesthetic trends have best manifested themselves and in which planning and design cultures could develop most widely. However, the periphery does not necessarily coincide with the geographical edges of the cities: both in Berlin and in Naples, historical events, or the particular topography have naturally shifted the "peripheral" location along a radius that only ideally starts from the city centre and often extends to its inner fringes. Rather, from a sociological point of view, the same interventions generally generate the peripheral condition, that is, marginalisation or social division. This, as we shall see, can be traced both on the large scale of the city and inside the neighbourhood. The materials are arranged in the following way: the text is introduced by a graphic and synthetic presentation of the historical context in Berlin and Naples and the documentation of the twelve case studies. In the second chapter, Comparison, which was mostly developed as the first by the young scholars involved in the project, three theoretical issues highlighted during the seminars are better presented: The ability of the project to involve the social level; the experimentalism of the interventions, in particular in construction technology, social approach and democratic participation; the relationship between public and private in the phases of implementation and the upkeep of the programmes. The third chapter, In-Depth Analysis, includes the contributions of the scientists involved to give a better articulated historical and critical analysis of many of selected case studies and of the wider urban and social context. The closing editorial paper offers a brief overview focusing on a selection of the theoretical nodes that emerged from the comparison of the materials from a contemporary perspective. The publication is the outcome of the homonymous research programme fully funded by DAAD German Academic Exchange Service and runned in 2019 in cooperation between the Technische Universität of Berlin, Department of Architecture (Habitat Unit) with the Università della Campania "Luigi Vanvitelli," Dipartimento di Architettura e Disegno Industriale in Aversa (Italy).